Clinical significance of aberrant DNA methylation in childhood acute lymphoblastic leukemia - Takeuchi, Seisho; Matsushita, Masahide; Zimmermann, Martin; Ikezoe, Takayuki; Komatsu, Naoki; Seriu, Taku; Schrappe, Martin; Bartram, Claus R.; Koeffler, H. Phillip (Leukemia research, 2011)
Methylation profile was analyzed in ninety-five patients with childhood acute lymphoblastic leukemia (ALL). Methylation of both MGMT and p16 genes were associated with higher age (p=0.01 and p=0.03, respectively). Methylation of both p15 and SHP1 genes occurred more frequently in T-ALL than in precursor B-ALL (p=0.02 and p=0.01, respectively). In contrast, methylation of the DAPK gene was more frequent in precursor B-ALL (p=0.01). Patients with methylation of multiple genes more likely had T cell phenotype, and are classified as medium/high risk (p=0.004 and p=0.03, respectively). These results suggest that methylation status is associated with clinicopathological features in childhood ALL.